Investigating the true nature of three hard X-ray sources. Issue 3 (19th August 2021) - Molina, M; Malizia, A; Masetti, N; Bassani, L; Bazzano, A; Bird, A J; Fiocchi, M; Palazzi, E; Ubertini, P
ABSTRACT: Many of the new high energy sources discovered both by INTEGRAL/IBIS and Swift/BAT have been characterized thanks to extensive, multiband follow-up campaigns, but there are still objects whose nature remains to be asserted. In this paper, we investigate the true nature of three high energy sources, IGR J12134−6015, IGR J16058−7253, and Swift J2037.2+4151, employing multiwavelength data from the near-infrared to the X-rays. Through Gaia and ESO-VLT measurements and through Swift /XRT X-ray spectral analysis, we re-evaluate the classification for IGR J12134−6015, arguing that the source is a Galactic object and in particular a cataclysmic variable. We were able to confirm, thanks to Nuclear Spectroscopic Telescope Array ( NuSTAR ) observations, that the hard X-ray emission detected by INTEGRAL/IBIS and Swift /BAT from IGR J16058−7253 is coming from two Seyfert 2 galaxies which are both counterparts for this source. Through optical and X-ray spectral analysis of Swift J2037.2+4151 we find that this source is likely part of the rare and peculiar class of symbiotic X-ray binaries and displays flux and spectral variability as well as interesting spectral features, such as a blending of several emission lines around the iron line complex.